Menyoal Kesehatan Mental Anak Korban Kekerasan Seksual - Saffana Maulidia; Ulin Nihayah; Ayu Wulandari; Richos Syaekhoni (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
Sexual violence is an act of coercion or threats from the perpetrator to the victim to perform sexual activity. Victims of sexual violence are used as objects to satisfy lust. Sexual crimes are not only committed by people far away but those closest to them can also be perpetrators. The impact of this sexual violence victim leaves a deep mental wound and the memory of being raped will never be forgotten. Sexual violence in Indonesia is an emergency and will only escalate if left unchecked. Therefore, this journal research aims to determine the causes, impacts, and therapies used to heal trauma victims of sexual violence in minors. The research method used in writing this journal is a qualitative descriptive analysis with case studies. From the results of the analysis, it is found that 1. Overcoming the trauma of sexual violence in mental health, therapy can be done through play therapy to express emotions that disturb the victim's mind and relieve anxiety and child trauma. 2. Provide social encouragement. 3. Reporting to the authorities.